Model-based Dynamic Optimal Control of an Ejector Expansion CO2 Heat Pump Coupled with Thermal Storages. (October 2018) - Liu, Fang; Deng, Jiaxin; Pan, Weiguo
Abstract: This study presents a model-based dynamic optimization strategy for charging of hot and cold thermal storages with a dual-mode CO2 ejector expansion heat pump, which could be used as a high-efficiency smart grid enabling option in heating and cooling services for buildings or industry. The dynamic model of this coupled system was developed by Modelica. The outlet water temperatures of hot and cold tanks are used as indicators in dynamic optimal control strategy. To optimize the overall performances during energy process, the transient performances are optimized by genetic algorithm based on dynamic model of system. Single-objective and multi-objective dynamic optimal control strategies were developed and applied for this system. Study results show that these two developed model-based dynamic optimal control strategies can optimize the overall performances of such coupled systems during energy charging. Compared with the control strategy with constant control parameters, these two dynamic optimal control strategies can be useful in the coordinative optimization of multiple control parameters, and multi-objective dynamic optimal control strategy is superior to the single-objective one.